Sleep quality during preparation for RAI: recombinant TSH vs. levothyroxine withdrawal - Markantes, Georgios K.; Dimitropoulos, Konstantinos; Armeni, Anastasia; Chrysanthopoulou, Niki; Georgiou, Konstantinos; Mamali, Irene; Georgopoulos, Neoklis A.; Theodoropoulou, Anastasia (Frontiers in Endocrinology, 2025)
BackgroundPatients with differentiated thyroid cancer (DTC) suffer from impaired sleep quality, which may be further impaired after radioactive iodine (RAI) treatment. The potential contribution of the type of preparation for RAI has not been studied. Our objective was to compare the effect of the types of preparation for RAI on the sleep quality of DTC patients, and to correlate sleep indices with hormonal and psychological parameters.Methodswe studied 104 DTC patients (76 women and 28 men) programmed to receive RAI, two to eight months after total thyroidectomy. Participants were classified into two groups, based on the type of preparation: 56 were prepared with levothyroxine withdrawal (LT4-W group) and 48 with recombinant human TSH (rhTSH) administration (rhTSH group). Assessment was done in the morning of RAI administration and included hormonal determinations (thyroid function tests, prolactin, cortisol, and adrenocorticotropic hormone) and evaluation of sleep quality (Pittsburg Sleep Quality Index-PSQI) and anxiety/depression levels (Hospital Anxiety and Depression Scale-HADS).ResultsThe two study groups did not differ in age and gender distribution, DTC histology, RAI indications and administered dose, thyroglobulin and anti-thyroglobulin antibodies levels. The rhTSH group demonstrated higher TSH and free thyroxine, and lower prolactin and cortisol; participants of this subgroup had better subjective quality (0.65 ± 0.71 vs 1.22 ± 0.92, p=0.002) and efficiency (0.35 ± 0.74 vs 0.72 ± 0.96, p=0.023), less daytime dysfunction (0.52 ± 0.59 vs 0.87 ± 0.82, p=0.03), and better global PSQI score (4.72 ± 3.32 vs 6.60 ± 3.99, p=0.014), while they also showed lower anxiety/depression scores compared to individuals in the LT4-W group (4.32 ± 4.22 vs 5.62 ± 3.85, p=0.046 and 3.55 ± 3.41 vs 5.86 ± 4.22, p=0.005, respectively). The between-groups differences in the above PSQI domains remained after correction for hormonal levels but disappeared (except for that in subjective quality) after correcting for anxiety/depression levels.ConclusionsIn DTC patients receiving RAI, preparation with rhTSH could contribute to better sleep quality compared to LT4 withdrawal. Increased depression and anxiety rather than differences in hormone levels seemed to mediate this difference.